A PHARMACEUTICO-ANALYTICAL STUDY OF AMRITADYA GUGGULU (AYUSHDHARA, 2020)
Aushadha Kalpana is prepared by different pharmaceutical processing applied to the crude drugs to get the desired therapeutic effects. Guggulu kalpana is one of them. Guggulu is the gummy resin of the Indian plant bdellium i.e. Commiphora mukul. Guggulu is always used after Shodhana to remove its impurities. So the process of Shodhana becomes imperative in different media. In addition to it, Shodhana of Guggulu in different media brings specific properties to Guggulu. Ayurvedic medicines are gaining increase in popularity worldwide for the treatment of various diseases in recent times. In the present study, Amritadya guggulu, one of the Guggulu preparation mentioned in Pidika, Bhagandara and Sthaulya like conditions in Chakkradatta, was prepared and analysed so as to prove the safety and efficacy of the drug. Aims and objectives: To develop standard operative procedure for preparation of genuine drug and to analyze the safety and purity of the drug. Material and Methods: Amritadya guggulu was prepared as per classical texts and analysed by using different parameters like organoleptic properties, physicochemical properties, TLC etc. Discussion and Conclusion: 50% weight loss was observed. The weight loss was due to removal of impurities present in the Guggulu and handling loss. Presence of low acid insoluble ash (1.08%) determines the presence of low adherent dirt as well as sand particles. Presence of low moisture content (loss on drying 6.2%) decreases decomposition and enhances the shelf life and therapeutic value of the drug. Hence it can be concluded that the pharmaceutical and analytical study confirm the authenticity and quality of the drug.